Pengaruh Penggunaan Motor Modifikasi (Tassi) Terhadap Tingkat Pendapatan Petani Di Desa Salo Dua Kec. Maiwa Kab. Enrekang - Samsuddin Samsuddin; Adnan Adnan; Hamka Hamka (Lembaga Pengembangan Kinerja Dosen, 2024)
The majority of the population in Salo Dua village, Maiwa sub-district, Enrekang district is engaged in farming. The production and price of farm products do not guarantee farmers a high income from farming activities, due to the process of transporting from the plantation to the location of collecting farm products with a modified tassi motorbike. This study aims to determine the use of motorbike tassi on the level of income and the level of performance of farmers. The results showed that the use of tassi motorbike in Salo Dua Village, Maiwa District, Enrekang Regency, there were independent variables simultaneously affecting farmers' income (Y) significantly. Partially, the tariff / fee variable (X1) has a positive but insignificant effect on farmer income (Y). While the variables of satisfaction (X2) and performance (X3) have a positive and significant effect on farmers' income (Y). The use of motor tassi can affect the performance of farmers, with 47.62% of respondents very able to ease the work of farmers in agricultural activities, be it harvesting or delivering fertiliser to farmer gardens that are difficult to reach by four-wheeled vehicles. 54.76% of respondents said the farmer's harvest process was more effective and efficient, 44.05% of respondents said farmers were greatly helped in the harvest process.